Numerical investigation of energy tunnel lining ground heat exchangers in a mountain environment. Issue 7 (October 2021) - Li, Chenglin; Zhang, Guozhu; Xie, Yongli; Liu, Xiaohua; Cao, Shiding
Abstract: The energy tunnel lining ground heat exchangers (GHEs) is a new technology to extract geothermal energy. At present, the researches on the feasibility of energy tunnel lining GHEs design are rare. In order to evaluate the feasibility of energy tunnel lining GHEs design in a mountain environment, a 3D numerical model was developed to simulate the transient heat transfer of energy tunnel lining GHEs. In this model, the inlet temperature varied with time based on the building refrigeration load, the numerical results were verified with the field monitoring data. According to the relationship between outlet temperature and the energy efficiency ratio (EER) of heat pump, the numerical results of outlet temperature were used to calculate the EER. Then, the energy efficiency of energy tunnel lining GHEs was evaluated. The results show that the design of the energy tunnel lining GHEs with a pipe pitch of 0.6 m and a pipe length of 329.4 m is feasible. Under continuous operation mode, the energy efficiency ratio reaches 4.44 and the refrigeration power reaches 175 kW in summer.